ANALISIS PERLAKUAN AKUNTANSI PIUTANG MURABAHAH PT BRI SYARIAH CABANG SIDOARJO - Sari, Dian Anggraini Kartika (Jurnal Akuntansi AKUNESA, 2013)
Manyfinancingin Islamic banksofferedto the publictoassistthe passage ofeconomy. For example,themurabahah, musharakaandmudharaba. Murabahahis ashort-termfinancing, and has small risks, thusmurabahahfinancingis in great demandbythe public. Murabahah has accounting treatment thatarealreadydefinedinSFASNo.102. Therefore, the aimof this studywasto analyzewhetherthe implementation of accounting of murabahahreceivablesare appropriate withSFASNo.102. Research method used is qualitative method. The resultof analysis ofthe accounting treatment ofmurabahahreceivables in BRIShariah Sidoarjois atreatment, disclosure, presentationandrecognition ofthemurabahareceivablespracticedinBRIShariah is appropriate withSFASNo.102 and theories. Keywords: murabahahreceivables, accounting treatment